CO2 Electroreduction in Ionic Liquids - Faggion, Deonildo; Gonçalves, Wellington D. G.; Dupont, Jairton (Frontiers in Chemistry, 2019)
CO2 electroreduction is among the most promising approaches used to transform this green-house gas into useful fuels and chemicals. Ionic liquids (ILs) have already proved to be the adequate media for CO2 dissolution, activation, and stabilization of radical and ionic electrochemical active species in aqueous solutions. In general, IL electrolytes reduce the overpotential, increase the current density, and allow for the modulation of solution pH, driving product selectivity. However, little is known about the main role of these salts in the CO2 reduction process, in particular, the assumption that ILs form solvent-separated ions. However, most of the ILs in solution are better described as anisotropic fluids and display properties of an extended cooperative network of supramolecular species that strongly reflects their mesoscopic and nanoscopic organization, inducing different processes in CO2 reduction compared to those observed in classical electrolyte solutions. The major aspects concerning the relationship between the structural organization of ILs and the electrochemical reduction of CO2 will be critically discussed in light of selected recent examples.